The Association between Intimate Partner Rape and Victimisation from Intimate Partner Controlling Behaviour and Physical Aggression in a Ugandan Sample - Brendah Nakyazze; Karin Osterman; Kaj Bjorkqvist (Journal of Educational, Health and Community Psychology, 2022)
The aim of the study was to investigate the relationship between victimisation from intimate partner rape and two types of intimate partner aggression. A questionnaire was completed by 609 females and 420 males in Uganda. The age range was between 16 and 94 years. The mean age was 31.5 (SD 10.9) for females, and 34.4 (SD 11.3) for males. The questionnaire included scales for measuring the frequency of victimisation from intimate partner rape, controlling behaviour, and physical aggression from an intimate partner. Females had been significantly more often victimised from intimate partner physical aggression than males. No significant difference was found between females and males on victimisation from intimate partner controlling behaviour. Victimisation from physical aggression and controlling behaviour from a partner were also highly correlated with each other for both females and males. Respondents who had been more than average victimised from intimate partner rape scored significantly higher than others on victimisation from intimate partner controlling behaviour and intimate partner physical aggression. The association between victimization from intimate partner rape and victimisation from intimate partner controlling behaviour and physical aggression followed the same pattern for females and males.